1996
DOI: 10.1111/j.1151-2916.1996.tb09048.x
|View full text |Cite
|
Sign up to set email alerts
|

New Processing Technique for Hydroxyapatite Ceramics by the Hydrothermal Hot‐Pressing Method

Abstract: A new processing technique for preparing hyroxyapatite (HAp) ceramics has been developed using the hydrothermal hot‐pressing (HHP) method. Powder mixed dibasic calcium phosphate dihydrate and calcium hydroxide mixed with a Ca/P ratio of 1.67 was treated at 150°C and 40 MPa. The HHP method with the selection of the powder enabled the HAp to be solidified at the low temperature. The resulting HAp ceramics had a tensile strength of approximately 10 MPa. Furthermore, the HAp ceramics possessed a lamellar microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 14 publications
1
31
0
1
Order By: Relevance
“…The maximum tensile strength values for the MgHA3 precursors (6 mol % Mg, nominal average size of 20 nm) are consistent with those reported for the densification of HA pellets under HHP conditions reported in the literature [25,27]. Based on these results, we suggest that the tensile strength attained for MgHA powders resulted from the cohesion and packing of particles during the dissolution-recrystallisation mechanism under HHP densification conditions.…”
Section: Microstructural Aspects and Mechanical Strength Of Mgha Compsupporting
confidence: 79%
See 2 more Smart Citations
“…The maximum tensile strength values for the MgHA3 precursors (6 mol % Mg, nominal average size of 20 nm) are consistent with those reported for the densification of HA pellets under HHP conditions reported in the literature [25,27]. Based on these results, we suggest that the tensile strength attained for MgHA powders resulted from the cohesion and packing of particles during the dissolution-recrystallisation mechanism under HHP densification conditions.…”
Section: Microstructural Aspects and Mechanical Strength Of Mgha Compsupporting
confidence: 79%
“…Some studies have focused on the selection of the solvent medium and its concentration to obtain in-situ crystallisation of elongated submicron-sized HA crystals using mixtures of Ca(OH) 2 with either dibasic calcium phosphate dihydrate (DCPD) [19] or octacalcium phosphate (OCP) [26] as precursors. Few studies have reported that after reacting these compounds with water and ammonia solutions, HA crystals grow perpendicularly in the direction of the applied loading pressure, producing a dense lamellar microstructure with high tensile strength [19,27]. Recently, the chemical reactivity of pure and calcium deficient submicron-sized HA powders with water under HHP conditions was examined using 10 to 20 wt% of water, temperatures between 100 and 200 ºC, and loading pressures between 15 and 60 MPa for reaction intervals between 12 and 24 h [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pores resulting from this method are often irregular in size and shape and not fully interconnected with one another. [415]. In another approach, bi-continuous water-filled microemulsions have been used as pre-organized systems for the fabrication of needle-like frameworks of crystalline HA (2 °C, 3 weeks) [416,417].…”
Section: Porositymentioning
confidence: 99%
“…It is known that the water of crystallization in calcium hydrogen phosphate dihydrate (CaHPO 4 ・2H 2 O; DCPD) is slowly lost below 100˚C [Peelen et al, 1991]. If the released water can be utilized as a reaction solvent during the HHP treatment, it is to be expected that the joining HA to metal can be achieved simultaneously under the hydrothermal condition, in addition to the synthesis and solidification of HA through the chemical reaction as follows [Hosoi et al, 1996]: 6CaHPO 4 ・2H 2 O + 4Ca(OH) 2 → Ca 10 (PO 4 ) 6 (OH) 2 + 18H 2 O…”
Section: Introductionmentioning
confidence: 99%